Organic Phototransistor Photonic Synapses for Artificial Vision - Ding, Feng; Xue, Di; Chi, Lifeng; Huang, Lizhen (Nano-Micro Letters, 2026)
The von Neumann architecture faces significant limitations, including low transmission efficiency and high energy consumption, when handling large-scale data and unstructured problems. Benefiting from the inherent merits of optical signals including high bandwidth, near-zero Joule heating, fast transmission speed, and immunity to electromagnetic interference, photonics provides a powerful pathway for high-speed neuromorphic computing. Together with the mechanical flexibility and largearea manufacturability of organic semiconductors, organic phototransistor (OPT)-based photonic synapses have therefore attracted extensive attention in recent years. This review provides a comprehensive overview of recent advances in OPT-based photonic synapses, covering operational principles, active materials, advances in bidirectional photoresponse process, as well as cutting-edge applications. Finally, the current challenges and opportunities in this field are highlighted. Distinct from previous reviews, this review emphasizes an in-depth exploration of bidirectional photoresponse mechanisms, a systematic dissection of material–structure–function correlations enabling integrated sensing-memory technology, and emerging. Highlights: 1 The latest progress in neuromorphic artificial synapses based on organic phototransistors is reviewed from three aspects: functional semiconductor materials, operating behaviors, and frontier applications/advancements. 2 The negative photoconductance behavior of novel phototransistors is discussed, along with their fascinating information-erasing capabilities demonstrated in organic photonic synapses. 3 Frontier applications and advancements in neuromorphic vision driven by organic photonic synapses, such as human visual adaptation, polarization-sensitive detection, high-dimensional reservoir computing, and multimodal neuromorphic encryption, are demonstrated.